2023
DOI: 10.1242/jcs.261160
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 prevents precocious Rho1 activation during cytokinesis in a Pak1-dependent manner

Abstract: During cytokinesis a series of coordinated events partition a dividing cell. Accurate regulation of cytokinesis is essential for proliferation and genome integrity. In fission yeast, these coordinated events ensure that the actomyosin ring and septum start ingressing only after chromosome segregation. How cytokinetic events are coordinated remains unclear. The GTPase Cdc42 promotes recruitment of certain cell wall-building enzymes while the GTPase Rho1 activates these enzymes. We show that Cdc42 prevents early… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Of note, the biosensor also integrates activities of the closely related RhoB and RhoC, which were shown to partially compensate for RhoA during cytokinesis. 35 Recently, it was reported that timely activation of the RhoA homolog in yeast is dependent on Cdc42, 36 toward which DLC3 also shows some GAP activity. 12 , 37 In addition, previous studies have described the binding of specific lipid species to DLC1 through the PBR directly adjacent to the GAP domain and the carboxyterminal StAR (steroidogenic acute regulatory)-related lipid transfer (START) domain, regulating its GAP activity.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the biosensor also integrates activities of the closely related RhoB and RhoC, which were shown to partially compensate for RhoA during cytokinesis. 35 Recently, it was reported that timely activation of the RhoA homolog in yeast is dependent on Cdc42, 36 toward which DLC3 also shows some GAP activity. 12 , 37 In addition, previous studies have described the binding of specific lipid species to DLC1 through the PBR directly adjacent to the GAP domain and the carboxyterminal StAR (steroidogenic acute regulatory)-related lipid transfer (START) domain, regulating its GAP activity.…”
Section: Discussionmentioning
confidence: 99%